Burnout in primary healthcare physicians and nurses in Turkey during COVID-19 pandemic. (9th January 2023) - Ayaslıer, Ata Arda; Albayrak, Beyza; Çelik, Esra; Özdemir, Özgür; Özgür, Özlem; Kırımlı, Emrah; Kayı, İlker and Sakarya, Sibel
Abstract: Background: Due to additional responsibilities and uncertainties during the COVID-19 pandemic, primary healthcare (PHC) workers are at increased risk of burnout. Aim: To determine and compare the burnout levels and related factors in PHC nurses and family physicians (FPs) during the COVID-19 pandemic. Methods: An online survey was delivered to PHC workers. Non-random sampling method was used. To evaluate burnout, the Maslach Burnout Inventory was used, which investigates burnout in three categories: emotional exhaustion (EE), depersonalization (DP) and reduced personal accomplishment (PA). Multivariate linear regression was used to analyze factors associated with burnout for FPs and nurses separately. Findings: Among the participants, 55.7% were nurses, the mean age was 42.34. FPs and nurses experienced similar levels of burnout in terms of EE. Family physicians had higher levels of low PA and DP. Based on the results of the multivariate analysis, while higher EE levels were significantly associated with unequal distribution of workload and communication problems within the Family Health Center for physicians, the unequal distribution of PPE, lack of appreciation by patients or colleagues and restrictions on work-related rights were relevant factors for nurses. Lack of appreciation and restrictions of the rights were associated with increased DP scores in both groups. Unequal distribution of workload was also associated with reduced PA among FPs. Conclusion: PHC physicians and nurses are affected by burnout in different ways under the conditions of the COVID-19 pandemic based on gender, socioeconomic status and working conditions. To protect the mental health of PHC workers in the next public health emergency, clarification in the organization of services, empowering PHC workers in emergency risk communication and provision of timely, adequate and free PPE is essential. It is also crucial to ensure the rights of health workers through macro policy changes especially during emergencies.